KONSEKUENSI EKONOMI DAN PROSES POLITIK DALAM PENYUSUNAN STANDAR AKUNTANSI - Adam, Helmy (Fakultas Ekonomi, UIN Maliki Malang, 2006)
Accounting standard setting merely is not a simple process because its standard regulatory approach should accommodate the interest of related parties. This interest is related to economic consequence caused by implementation of accounting standard which will be a reason of the battle of political process or politicization of accounting standard. Hence, existing argue about the attempt of related parties is associated to utility maximization standard in order to get most benefit standard, although in many cases like in China reflected government interest to keep their political ideology.